PREPARATION OF HYDROXYAPATITE POWDERS FOR MEDICALAPPLICATIONS VIA SOL-GEL TECHNIQUE - Iis Sopyan (Center for Science & Technology of Advanced Materials - National Nuclear Energy Agency, 2003)
PREPARATION OF HYDROXYAPATITE POWDERS FOR MEDICALAPPLICATIONS VIA SOL-GEL TECHNIQUE. Hydroxyapatite (HA) powders have been prepared via sol-gel procedure using calcium nitrate tetrahydrate and di-ammonium hydrogen phosphate as the precursors for calcium and phosphorus, respectively. An ammoniacal solution of the monomers was heated at 100°C for about 3 –4 h until a white gel of hydroxyapatite mixture were obtained. The obtained gel was then dried at 340°C for 7 h and subsequently subjected to an 820°C calcination for 2 h. The yield of the powder mixture ranged between 50 to 53 g. XRD measurement shown that the powder contained hydroxyapatite crystal with b-TCP ( 15-20%) and calcium oxide (4-6%) as secondary phases. Further treatment was conducted to gain hydroxyapatite powder of higher purity, thus the correct Ca/P ratio, by adding an appropriate amount of di-ammonium hydrogen phosphate and heated while stirring at 90°C for 4 h. Good purity (almost 100%) of the obtained hydroxyapatite was confirmed by XRD analysis.This result proved that our HA powder meets the medical prerequisite: a HA purity of above 95%. Morphological evaluation by SEM measurement shows that the particles of the HA agglomerate are globular in shape with an average size of 1-2 mm in diameter. Meanwhile, the primary particles have a diameter of 70-150 nm in average. Surface area of the powder is 7 m2/g and the mean particle size as measured using X ray sedimentation method is ca. 1 mm. The measurements are not in good agreement with the morphological investigation. We consider, accordingly, that the particles presumably have high surface potentials, thus forming very tightly bonded agglomerates